Diseño del cuadro de mando integral o (balanced scorecard) para la compañía de transporte pesado “Lamanence” s.a de la provincia de Cotopaxi, del cantón La Mana correspondiente al periodo octubre 2014 a febrero del 2015 - García Quevedo, Josefa (2015)
The thesis that is presented for our graduation proposes the Design of Scorecard or (Balanced Scorecard) for Heavy Transport Company "Lamanence SA". The same serving as a control tool to achieve improvement in each of the departments of the Company, which would transform the management of our institution, using strategies of monitoring and control through the four basic perspectives such as: Financial, Customer, Internal Processes, Learning and Growth. That methodology translates strategy into a set related with indicators to achieve the institutional vision. The first chapter contains the theoretical related to each of the main categories starting with the company, administrative process, strategic planning….